Senegal : Seventh Review under the Policy Support Instrument and Request for Modification of Assessment Criteria. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Senegal's Seventh Review Under the Policy Support Instrument (PSI) and Request for Modification of Assessment Criteria. GDP growth was lower than expected in 2013 but would increase to 4.9 percent in 2014 with a rebound in agriculture, mining, and industry. All quantitative assessment criteria and indicative targets for end-2013 were met, including on the budget deficit despite a significant revenue shortfall. Structural reform implementation has been slow, with many benchmarks met after their respective deadlines. Despite challenging prospects for 2014, the authorities intend to continue reducing the deficit. The IMF staff recommends completion of the seventh PSI review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet